Scar Endometriosis - A Case Report: Life Sciences -Gynecology - Bose, Preethi; R, Varrshine; J, Thanka (International Journal of Life Science and Pharma Research, 2023)
Endometriosis is a common disease affecting women in the reproductive age group. Endometriosis is the presenceand growth of functional endometrial tissue at sites other than the uterus. Scar endometriosis, a type of extrapelvicendometriosis, is the presence of functioning endometrial tissue in the abdominal wall along the scars of previous abdominalsurgeries. About 1-2 % of women who underwent cesarean section have the risk of developing surgical scar endometriosis.We report the case of a 27-year-old woman with a history of two cesarean sections. She presented with pain abdomen and anabdominal lump, which increased during menstruation. On examination, there was a tender lump in the abdomen. A clinicaldiagnosis of scar endometriosis was made. Radiological investigations confirmed the diagnosis. Under anesthesia, the scarendometriosis tissue was removed by wide excision and sent for histopathology, which confirmed the presence of endometrialglands with stroma. The patient was discharged and followed up without any recurrence. This case is reported as a rarecondition, though it is increasing in incidence. The clinical features may mimic many surgical or dermatological conditions;hence there is a high chance of misdiagnosis and unnecessary referral, causing physical and emotional distress to the patient.Basic knowledge of the condition, thorough clinical examination, and radiological imaging are usually effective in diagnosing thecondition. Surgical excision and follow-up form the basis of treatment of scar endometriosis. Though surgery is the mainstay oftreatment and medical treatment does not provide a permanent cure, there is scope for future research to discover innovativemedical methods to provide a permanent cure without surgery. The preventive aspect is also important for the surgeon doingthe primary surgery. However, further evidence-based studies are needed to establish effective methods to prevent thedevelopment of scar endometriosis.